2021
DOI: 10.1002/adpr.202100055
|View full text |Cite
|
Sign up to set email alerts
|

Photosaturation in Luminescent LuAG:Ce Garnet Concentrator Rods

Abstract: The luminescence efficiency of Ce3+ in garnet phosphors is among the most stable for luminescent materials. Still, it has been observed to be reduced at high incident blue flux (known as droop) due to nonlinear processes caused by the high lumen density inside the materials. Herein, it is shown that in the case of Ce3+‐doped garnet concentrator rods, the droop can be explained by excited‐state absorption (ESA) of mainly green Ce3+ luminescence light that is trapped inside the rods. ESA spectroscopy and thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Modified HDFT‐PBE0 ( α = 0.28, μ = 0) 41–43 calculations are performed to overcome the underestimation of the bandgap by the standard DFT calculations and to obtain the improved electronic structure. The Γ → Γ direct bandgap of LuAG is calculated to be 7.89 eV from PBE0 calculation, in consistence with the experimental bandgap energy (7.9–8.2 eV) 44,45 . It is indicated that our obtained GKS gap provides a reasonable estimation on the fundamental gap.…”
Section: Experimental Process and Computational Methodologysupporting
confidence: 77%
See 1 more Smart Citation
“…Modified HDFT‐PBE0 ( α = 0.28, μ = 0) 41–43 calculations are performed to overcome the underestimation of the bandgap by the standard DFT calculations and to obtain the improved electronic structure. The Γ → Γ direct bandgap of LuAG is calculated to be 7.89 eV from PBE0 calculation, in consistence with the experimental bandgap energy (7.9–8.2 eV) 44,45 . It is indicated that our obtained GKS gap provides a reasonable estimation on the fundamental gap.…”
Section: Experimental Process and Computational Methodologysupporting
confidence: 77%
“…The Γ → Γ direct bandgap of LuAG is calculated to be 7.89 eV from PBE0 calculation, in consistence with the experimental bandgap energy (7.9-8.2 eV). 44,45 It is indicated that our obtained GKS gap provides a reasonable estimation on the fundamental gap. Our calculated projected DOSs of LuAG in Figure 2 indicates that the dominant components of the valence and the conduction band edge states are O-2p and Lu-5d orbitals, respectively.…”
Section: Computational Methodologymentioning
confidence: 51%